The Influence of Communication and Employment Status on Employee Work Effectiveness - Juliharta, I Dewa Gede Agung Kurnia; Zaharuddin, Zaharuddin; Sahim, Aswin Naldi; Supriyadi, Supriyadi (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
The progress of an organization can be seen from changes towards the good, especially in achieving the goals that have been set, both private organizations and government agencies, will not be separated from the support of human resources owned by the organization. This study aims to reveal: 1) Is there an influence of communication on employee work effectiveness; 2) Is there an influence of employee status on employee work effectiveness.; 3) Is there an influence of communication and employee status together on employee work effectiveness. The method used in this study is quantitative with a survey approach. The population of this study were employees at the Directorate of Research and Community Service (DPPM) of the Ministry of Higher Education, Science, and Technology. The sampling technique used in this study was random sampling. Research data were obtained through the Communication, Employee Status and Work Effectiveness instruments. The results of the study 1) Communication has a significant effect on employee work effectiveness at DPPM of the Ministry of Higher Education, Science, and Technology.; 2) Employee Status has an effect but is not significant on Employee Work Effectiveness at DPPM of the Ministry of Higher Education, Science, and Technology.; 3) Communication partially has a significant influence, while Employment Status does not have a significant influence.